(untitled) (Journal of Parents and Teachers, 2014)
Adolescence is an evolutionary period of transition between childhood and youth, in which the experiences lived will have a significant impact on the individual. Some fundamental characteristics of this stage are: the adolescent is socially expansive, lives from impacts and impressions, is radical and dogmatic, is often in a state of frustration, etc. The article lists up to 15 characteristic features of the adolescent stage in which we are shown, for example, that the adolescent is burdened with emotional instability that translates into unrealistic ideals, which can only be achieved through family independence. In relation to educators and families, faced with this vulnerable stage, it is recommended that we approach reality by being patient and active.